Empirical factors in increasing return on assets at islamic banks in Indonesia - Mina Wati Dewi; Akhmadi Akhmadi; Wawan Ichwanudin (International Journal of Applied Finance and Business Studies, 2023)
The purpose of this study is to develop a research model to overcome business phenomena and research gaps between Operating Costs and operating Income and NonPerforming Financing on Return on Asset with Funding to Deposit Ratio as a mediating variable at Islamic Commercial Banks in Indonesia (Case Study on Islamic Commercial Banks in Indonesia listed on the IDX in 2016-2020). The data collection method used is literature study and documentation study. Sampling using the saturated sampling method obtained as many as 11 Islamic banks. The available data has met the requirements for using multiple linear regression equation models. Hypothesis testing uses a significance test (t-test), coefficient of determination test (R2), and SPSS test. Coefficient of determination (R2) and Sobel test. The results of this study indicate that Operating Expenses and Operating Income have a negative and significant effect on Return on Assets, and the Funding Deposit Ratio has no considerable impact on Return on Assets. At the same time, Operating Costs and operating Income have no significant effect on the Deposit Ratio. Intervening Funding to Deposit Ratio cannot mediate the relationship between Operating Costs and operating Income with Return on Assets. In addition, the author hopes this research can theoretically contribute to the financial management and banking literature in this context.